The Chinese Reassessment of Socialism, 1976-1992 - Sun, Yan (Book collections on Project MUSE., 2001)
A momentous debate has been unfolding in China over the last fifteen years, only intermittently in public view, concerning the merits of socialism as a philosophy of social justice and as a program for national development. Just as Deng Xiaoping's better advertised experiment with market- based reforms has challenged Marxist-Leninist dogma on economic policy, the years since the death of Mao Zedong have seen a profound reexamination of a more basic question: to what extent are the root problems of the system due to Chinese socialism and Marxism generally? Here Yan Sun gathers a remarkable grou.